Atypical Presentation of Multiple Myeloma: From Heart Failure to Multiple Myeloma - Sohaimi, Ainur Elliana; Jamhuri, Nur Syazwani; Ibrahim, Ismail; Salim, Hotimah Masdan (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Multiple myeloma (MM) is a hematological malignancy commonly associated with bone pain, hypercalcemia, and renal failure. However, its presentation can occasionally mimic other medical conditions, which may delay diagnosis. This case report describes a patient who was initially diagnosed and treated for heart failure but was later found to have MM, highlighting the importance of considering MM in the differential diagnosis of heart failure. A 56-year-old lady presented with recurrent episodes of shortness of breath, orthopnea, paroxysmal nocturnal dypsnea and bilateral lower limb swelling which she had been treated for decompensated heart failure with optimal therapy. She denied any family history of cardiovascular disease personal history of underlying medical condition and was a nonsmoker. This patient was diagnosed with multiple myeloma and probability of concomitant cardiac amyloidosis and commenced on bortezomib, thalidomide and dexamethasone (VTD) regime and standard optimal therapy of heart failure but her condition deteriorated. After a few days of starting chemotherapy, patient demised despite all the resuscitative effort. Multiple myeloma is common hematological malignancy with its distinct clinical features of “CRAB”, however, more attention and alertness should also be exercised by clinicians as to be able to diagnose it early.